2021
DOI: 10.1038/s41598-021-87528-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lipid-lowering therapy on coronary plaque regression: a systematic review and meta-analysis

Abstract: To assess the influence of lipid-lowering therapy on coronary plaque volume, and to identify the LDL and HDL targets for plaque regression to provide a comprehensive overview. The databases searched (from inception to 15 July 2020) to identify prospective studies investigating the impact of lipid-lowering therapy on coronary plaque volume and including quantitative measurement of plaque volume by intravascular ultrasound after treatment. Thirty-one studies that included 4997 patients were selected in the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Previously published pooled analyses have established the role of LLTs on plaque regression [70] , [71] , [72] , [73] . However, most pooled analysis to date were rather conservative in the type of LLT included and did not account for the level of lipids at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published pooled analyses have established the role of LLTs on plaque regression [70] , [71] , [72] , [73] . However, most pooled analysis to date were rather conservative in the type of LLT included and did not account for the level of lipids at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“… Plaque Significant enhancing factors Established ASCVD. Studies have shown that reversal of plaque begins when LDL-C falls below approximately 60–80 mg/dl and treatment is begun before significant scarring and calcification occurs [246] , [247] , [248] . That should also make new intimal thickening, plaque and intraarterial thrombi much less likely, if blood pressure and all other factors are well controlled.…”
Section: Despite Many Recommendations Early Treatment Has Not Become ...mentioning
confidence: 99%
“…5 Intravascular ultrasound evidence suggests that plaque regression occurs when LDL-C is lowered to < 70-80 mg/dL. 6 Moreover, studies of individuals with genetic variants in genes encoding proteins that regulate LDL-C levels have revealed that the strength of the relationship between LDL-C and cardiovascular risk is time dependent. 3 For example, people with a loss-of-function variant in the gene encoding for PCSK9, such as a nonsense mutation, that results in a reduction in LDL-C have up to an 88% lower risk of CHD (myocardial infarction, fatal CHD, or coronary revascularization) because lower LDL-C is present since birth.…”
Section: Introductionmentioning
confidence: 99%